The role of 3D printed heart models in immediate and long-term knowledge acquisition in medical education - Lau, Ivan; Sun, Zhonghua (MedReviews, 2022)
Background: The long-term effect of three-dimensional printed heart model (3DPHM) on knowledge acquisition of congenital heart disease (CHD) remains unknown. This prospective cohort study aims to investigate the role of 3DPHM in improving immediate knowledge gain and long-term knowledge retention on CHD among the medical students.